Perancangan Bisnis Untuk Jasa Videografi Hue Production - Ricky Wijaya; Ellen Saputra (Universitas Ciputra Surabaya, 2018)
The purpose of this research is to know the interest of target market on videography services in Surabaya. The research method used in this research is quantitative and qualitative research methods. Quantitative research method is an online questionnaire with 100 respondents domiciled in Surabaya, while qualitative research methods includes interviews with experts and videography services users as well as literature studies of books and journals related to videography, social media and marketing. The results concluded that teenagers to adults today have a great interest in using videography services, especially on video documentation of events, weddings and company profiles.